Indigenous parents and child welfare: Mistrust, epistemic injustice, and training - Leckey, Robert; Schmieder-Gropen, Raphael; Nnebe, Chukwubuikem; Clouthier, Miriam (Social & Legal Studies, 2022)
The settler state's taking of Indigenous children into care disrupts their communities and continues destructive, assimilationist policies. This article presents the perceptions of lawyers, social workers and judges of how Indigenous parents experience child welfare in Quebec. Our participants characterized those experiences negatively. Barriers of language and culture as well as mistrust impede meaningful participation. Parents experience epistemic injustice, wronged in their capacity as knowers. Mistrust also hampers efforts to include Indigenous workers in the system. Emphasizing state workers’ ignorance of Indigenous family practices and the harms of settler colonialism, participants called for greater training. But critical literature on professional education signals the limits of such training to change institutions. Our findings reinforce the jurisdictional calls away from improving the system towards empowering Indigenous peoples to run services of child welfare. The patterns detected and theoretical resources used are relevant to researchers of other institutions that interact with vulnerable populations.
Keywords: 2000 à aujourd'hui; 2020-2029; amériques; approches et analyses; australie; canada; care; cours; cycles supérieurs; discipline; droit; enfants autochtones; fem9000; injustice; inégalités; nouvelle-zélande; océanie; politique assimilationniste; périodes historiques; racisme; régions géographiques; santé; science politique et droit; sciences humaines; sciences sociales; système colonial; systèmes d'oppressions; thématiques; violences; états coloniaux

Les disparitions de filles et de femmes autochtones à Tiohtiá:ke/Montréal : pour une collaboration réelle entre le SPVM et les milieux autochtones - Femmes autochtones du Québec; Bernier, Dominique; Farget, Doris; Trilsch, Mirja (2020)
Le présent rapport de recherche s’inscrit dans les mobilisations autour de l’enjeu public que représentent les disparitions et les assassinats de femmes ou de filles autochtones au Canada. Considérant que l’autochtonie urbaine est un phénomène important au Québec, que la majorité des cas de disparition et d’assassinat de filles et de femmes autochtones ont lieu en milieu urbain et qu’il existe un manque patent de données portant spécifiquement sur Tiohtiá:ke/Montréal, le présent rapport examine cette « crise sociale » au sein de cet espace urbain. L’objectif de la recherche est de comprendre la réponse du Service de police de la ville de Montréal (SPVM) face à ces disparitions et assassinats. Bien que nos données démontrent qu’il y a consensus autour de la nécessité d’une collaboration entre le SPVM et les organisations communautaires et autochtones pour aborder de manière efficace la problématique, nous avons également constaté de nombreuses difficultés entourant la relation et la collaboration entre le SPVM et les personnes concernées par les disparitions et les assassinats de femmes et de filles autochtones. Des entretiens réalisés auprès de membres du SPVM et d’intervenants et intervenantes et une analyse du discours des personnes participantes, nous permettent de mettre en lumière les différentes dimensions des difficultés dans cette relation de collaboration. Nous soutenons que non seulement le phénomène des femmes et filles autochtones disparues et assassinées doit être saisi en tenant compte du cadre juridique des droits humains, mais la réponse à cette situation de la part des autorités doit également s’y conformer. C’est aussi dans ce cadre que sont formulées les huit recommandations finales adressées au SPVM et aux autorités publiques.
Keywords: amériques; approches et analyses; canada; cours; discipline; disparition; droit; droits des femmes*; droits des femmes* autochtones; histoire et politique; intersectionnalité; montréal; pol4105; police; premier cycle; québec; racisme; régions géographiques; science politique et droit; sciences juridiques; sexisme; système colonial; systèmes d'oppressions; thématiques; tiohtiá:ke; violences

L'homophobie - Borrillo, Daniel; Mécary, Caroline (Que sais-je?, 2019)
« L'homophobie est l'attitude d'hostilité à l'égard des homosexuels, hommes ou femmes. Quelles sont ses origines ? Quels sont ses rapports avec les autres formes de stigmatisation et de discrimination ? Comment, et à partir de quels discours, la suprématie hétérosexuelle, ainsi que la dévalorisation corrélative de l'homosexualité, ont-elles été construites ? Existe-t-il une personnalité homophobe? Et par quels moyens peut-on lutter contre cette forme de violence ? »– Quatrième de couverture.
Section: 127 pages ; 18 cm.
Keywords: LGBTQIA2+; approches et analyses; cours; discipline; droit; histoire et politique; homophobie; hétérosexisme; premier cycle; science politique et droit; soc2014; systèmes d'oppressions; thématiques; violences

Sexualized Violence and Colonialism: Reflections on the Inquiry into Missing and Murdered Indigenous Women - Razack, Sherene (Canadian Journal of Women and the Law, 2016)
Introduction to the special isuue of the Canadian Journal of Women and the Law on the "Missing and Murdered Indigenous Women Conference".
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; canada; cours; discipline; droit; droits des femmes*; féminicide; intersectionnalité; justice sociale; pol4105; premier cycle; périodes historiques; racisme; régions géographiques; science politique et droit; sexisme; système colonial; systèmes d'oppressions; thématiques; violences

Infiltrated Intimacies: The Case of Palestinian Returnees - Shalhoub-Kevorkian, Nadera (Feminist Studies, 2016)
This essay examines Palestinian women’s struggles following the 1948 Nakba, when many challenged their uprooting by attempting to return back to their homes and land. Analyzing women’s narratives recounting their experiences from 1948 to 1953 within the context of the settler-colonial regime of control, the essay reveals Israel’s criminalization of the return of Palestinian refugees as acts of “infiltration,” and the unspoken gendered history of trauma that infiltrates the intimate space of women’s families, bodies, and lives. By sharing women’s voices and their embodied memories about childbirth, menstruation, intimate family life, their homes, and domestic life, the article works to provide gender analyses of the political work of suffering, to demonstrate how women were uniquely targeted and affected by such criminalization. Unmasking the political history of trauma and suffering and borrowing meanings from women cast out as illegal by the Israeli state, positions women returnees as frontliners against the political illegality and criminalization of settler colonialism.
Keywords: 1900-1999; 1940-1949; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; asie; cours; discipline; droit; féminisme arabe; féminisme décolonial; féminisme islamique; histoire et politique; israël; nakba; palestine; pol4212; premier cycle; périodes historiques; régions géographiques; science politique et droit; système colonial; systèmes d'oppressions; thématiques; violences

Normal life: Administrative violence, critical trans politics, and the limits of law - Spade, Dean (Duke University Press, 2015)
Attendez—qu'est-ce qui ne va pas avec les droits ? On suppose généralement que les personnes transgenres et non conformes au genre devraient suivre les stratégies de droits civils et «d'égalité» des organisations de défense des droits des lesbiennes et des homosexuels en faisant campagne pour des réformes juridiques qui garantiraient ostensiblement la non-discrimination et une protection égale devant la loi. Cette approche suppose que la meilleure façon de lutter contre la pauvreté et la criminalisation qui affligent les populations trans est d'obtenir une reconnaissance légale et une inclusion dans les institutions de l'État. Mais cette stratégie est-elle efficace ? Dans la vie normaleDean Spade présente des critiques révélatrices du cadre d'égalité juridique pour le changement social et pointe des exemples d'activisme trans populaire transformateur qui soulève des demandes qui vont au-delà des réformes traditionnelles des droits civiques. Spade explose les hypothèses sur ce que les droits légaux peuvent faire pour les populations marginalisées et décrit les processus et les formations de résistance transformatrice qui s'attaquent aux causes profondes du mal et de la violence. Dans la nouvelle postface de cette édition révisée et augmentée, Spade note l'intégration rapide de la politique trans et constate que ses prédictions selon lesquelles l'obtention d'une reconnaissance légale ne profitera pas aux populations trans se concrétisent. Spade examine les efforts récents de l'administration Obama et des défenseurs de l'égalité des trans pour "pinkwash" la violence d'État en articulant les systèmes militaires et pénitentiaires américains comme des sites pour les réformes d'inclusion des trans. Dans le contexte de la récente visibilité accrue des personnes trans et de la politique trans, Spade continue de plaider pour le démantèlement des systèmes de violence d'État qui raccourcissent la vie des personnes trans. Aujourd'hui plus que jamais, Normal Life est un appel urgent à la justice et à la libération trans, et aux transformations radicales que cela nécessitera.
https://public.ebookcentral.proquest.com/choice/publicfullrecord.aspx?p=2096555
Keywords: amériques; approches et analyses; cours; cycles supérieurs; discipline; discours dominant; droit; fem9000; identités LGBTQIA2+; militance; personnes trans*; ressource en ligne; régions géographiques; science politique et droit; systèmes d'oppressions; thématiques; violences; états-unis

“It Happened More Than Once”: Freezing Deaths in Saskatchewan - Razack, Sherene (Canadian Journal of Women and the Law, 2014)
Le présent article analyse les enquêtes et une commission sur des décès par hypothermie en Saskatchewan, au Canada. Il souligne les économies raciales et d’espace liées à ces décès, et il suggère que les relations structurelles propres au colonialisme de peuplement produisent et encouragent les expulsions continues et quotidiennes d’autochtones de la part des colonisateurs, expulsions qui sont inévitablement violentes. La ville coloniale appartient au colonisateur et son occupation est inévitablement récusée par la présence des autochtones dans la ville. L’autochtonité met mal à l’aise, car elle conteste la prétention du colonisateur à la légitimité en remettant en cause une fiction très tenace dans les états coloniaux selon laquelle les peuples autochtones seraient à l’agonie. La pratique qui consiste à repousser les autochtones aux périphéries de la ville vient du besoin des colonisateurs de maintenir les lignes de force des villes coloniales. Aujourd’hui, quand cette pratique est scrutée par le droit, comme ce fut le cas dans l’enquête sur le décès de Neil Stonechild, et dans des enquêtes sur les décès par hypothermie, elle est considérée soit comme le fait de quelques policiers sans vergogne ou encore on la nie carrément. Ce qui demeure dans les registres judiciaires, toutefois, ce sont les économies raciales d’espace dans la ville coloniale et la dévalorisation persistante de la vie autochtone, une dévalorisation que la loi produit et soutient. Dans la première partie, je présente des idées sur les économies raciales et d’espace de la ville coloniale. Dans la deuxième partie, j’étudie le cas du décès de Neil Stonechild, ainsi que la réponse du droit à ce décès, la Commission d’enquête Wright. Dans la troisième partie, j’analyse les enquêtes sur les décès par hypothermie de Rodney Niastus et de Lawrence Wegner, deux jeunes autochtones morts dix ans après Stonechild, et j’explore deux mouvements dans l’espace et le temps : Niastus et Wegner traversant la ville pour trouver la mort dans un champ gelé de la zone nord-ouest, et le cheminement que l’enquête nous invite à faire en nous faisant croire que Niastus et Wegner sont les seuls responsables de leur décès. Dans le panorama des décès d’autochtones en détention en Saskatchewan, y compris en prison, par suicide et à la suite de violents affrontements avec la police, le corps d’un autochtone est un corps qui ne peut être assassiné.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; canada; capitalisme; cours; discipline; droit; histoire et politique; hypothermie; justice sociale; meurtre; mort; personnes autochtones; pol4105; premier cycle; périodes historiques; racisme; régions géographiques; saskatchewan; science politique et droit; sciences de l'éducation; système colonial; systèmes d'oppressions; thématiques; violences

Prison sexual abuse: Race, gender, and the rule of law - Buchanan, Kim (Columbia University, 2010)
In this dissertation, I argue that the exemption of prisons from the rule of law fosters abusive institutional practices that reveal the race and gender dynamics of sexual abuse in prison and in the outside world. The first article, Beyond Modesty: Privacy in Prison and the Risk of Sexual Abuse, shows that Fourth Amendment privacy offers little protection against the cross-gender searches and surveillance that expose women prisoners to sexual abuse by male guards. It proposes a reinterpretation of Fourth Amendment privacy that would recognize a constitutional right to be free from the fear, risk and reality of prison sexual abuse. The second article, Impunity: Sexual Abuse in Women's Prisons, shows that an edifice of constitutional, statutory and common-law rules confers near-complete institutional immunity against nearly all prisoner claims of custodial sexual abuse. These immunity rules parallel those of historical status regimes which excluded low-status litigants from courts on the basis of race and gender, such as civil death, slavery, segregation and the common law of marriage and rape–with similar results: low-status women of color are exposed to systematic and institutionalized sexual abuse, and are prevented from seeking protection or redress from the courts. The third article, Our Prisons, Ourselves: Race, Gender and the Rule of Law, develops these insights in men's prisons. In the absence of enforceable external rules, staff and administrators often adopt a gendered practice of institutional governance that requires prisoners to prove their manhood by fighting, and penalizes unmanly men by allowing others to rape them. These unlawful gendered practices are obscured by a false but powerful racialized narrative: most people inside and outside prison believe, inaccurately, that prison rape is mainly black-on-white. By casting sexual violence as a "complex and intractable" race relations problem for which administrators are not to blame, the racial narrative bolsters the rationale for exempting prison administration from the rule of law. Thus the perception (and reality) of unchecked prison violence supplies a reason for courts not to interfere with the unlawful institutional policies that foster it.
https://clio.columbia.edu/catalog/8481765
Keywords: approches et analyses; criminologie; discipline; droit; genre; intersectionnalité; mémoires/thèses; racisme; ressource en ligne; science politique et droit; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences; violences sexuelles

Realizing the UN Declaration on the Rights of Indigenous Peoples: triumph, hope, and action - Joffe, Paul; Hartley, Jackie; Preston, Jennifer (Purich Pub., 2010)
Adopted by the UN General Assembly on 13 September 2007, the United Nations Declaration on the Rights of Indigenous Peoples affirms the “minimum standards for the survival, dignity and well-being of the indigenous peoples of the world.” The Declaration responds to past and ongoing injustices suffered by Indigenous peoples worldwide. It provides a strong foundation for improved relationships with states, and for the full recognition of the inherent rights of Indigenous peoples. Despite this, Canada was one of the few countries to oppose the Declaration. The contributors to this collection analyze the development of the Declaration, recall the triumph of its adoption, and illustrate the hopes and actions for its implementation. The discussion moves beyond Canadian borders to the international stage, providing accessible information and guidance on the Declaration and how it can be used to advance human rights. Policy makers, Indigenous communities, politicians, academics, lawyers, human rights advocates, NGOs, and anyone interested in the significance of the Declaration will find this to be a valuable resource. Contributors include Indigenous leaders, legal scholars and practitioners, state representatives, and representatives from NGOs, with extensive knowledge of and experience in Indigenous peoples’ human rights law, policy, and practice.
Le texte de McKay, M. C. et Benjamin, C. (2010). A vision for fulfilling the indivisible rights of Indigenous women a été donné en lecture au cours POL4105.
Keywords: 2000 à aujourd'hui; 2000-2009; ONU; amériques; approches et analyses; canada; capitalisme; cours; discipline; droit; droits des personnes autochtones; histoire et politique; justice sociale; pol4105; premier cycle; premiers peuples; premières nations; périodes historiques; régions géographiques; science politique; science politique et droit; système colonial; systèmes d'oppressions; thématiques; violences

Decoding Black Women: Policing Practices and Rape Prosecution on the Streets of Philadelphia - Irving, Toni (NWSA Journal, 2008)
Black women are generally displaced as victims of rape. The police response to the sexual assault of black women in general and lower-class black women in particular is illustrative of how sexual ideologies help construct complex social hierarchies that in turn structure rights. How the law currently deals with rape places black women outside of the narrative frames that legitimate entitlement. Rape continues to stand in for, and effectively obscure, other social, political, and economic concerns. Unpublished and often ignored, the rape narrative is a ripe site to supply oppositional interpretations of national experience and transmit some of the structural problems in the criminal justice system. Pulling from over two thousand “real” rape cases of low-income black women ignored and not investigated in Philadelphia between 1995 and 2000, this article reads black female rape narratives as case studies in order to discuss the way personal narratives of rape victims are structured by competing and overwhelming sociolegal narratives that undercut their reception. As the fastest growing prison population, the presence of the law to punish black women stands in stark contrast to the absence of the law to protect them.
Keywords: 1900-1999; 1990-1999; afro-féminisme; amériques; approches et analyses; arts; corps; cours; discipline; droit; droit des femmes* noires; droits des femmes*; féminisme afroaméricain; histoire et politique; intersectionnalité; inégalités; philadelphie; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; science politique; science politique et droit; sex2283; sexisme; systèmes d'oppressions; thématiques; viol; violences; états-unis; études littéraires

Only words - MacKinnon, Catharine A. (Harvard University Press, 1993)
When is rape not a crime? When it's pornography–or so First Amendment law seems to say: in film, a rape becomes "free speech." Pornography, Catharine MacKinnon contends, is neither speech nor free. Pornography, racial and sexual harassment, and hate speech are acts of intimidation, subordination, terrorism, and discrimination, and should be legally treated as such. Only Words is a powerful indictment of a legal system at odds with itself, its First Amendment promoting the very inequalities its Fourteenth Amendment is supposed to end. In the bold and compelling style that has made her one of our most provocative legal critics, MacKinnon depicts a society caught in a vicious hypocrisy. Words that offer bribes or fix prices or segregate facilities are treated by law as acts, but words and pictures that victimize and target on the basis of race and sex are not. Pornography–an act of sexual domination reproduced in the viewing–is protected by law in the name of "the free and open exchange of ideas." But the proper concern of law, MacKinnon says, is not what speech says, but what it does. What the "speech" of pornography and of racial and sexual harassment and hate propaganda does is promote and enact the power of one social group over another. Cutting with surgical deftness through cases of harassment in the workplace and on college campuses, through First Amendment cases involving Nazis, Klansmen, and pornographers, MacKinnon shows that as long as discriminatory practices are protected as free speech, equality will be only a word.
Section: 152 p. ; 19 cm
Keywords: 1900-1999; 1990-1999; amériques; approches et analyses; cours; discipline; droit; histoire et politique; patriarcat; premier cycle; périodes historiques; régions géographiques; science politique et droit; sciences humaines; sciences sociales; sex1911; sexisme; sexualité; sofia; systèmes d'oppressions; thématiques; violences; états-unis; études de genres

Les femmes autochtones et la justice pénale - Jaccoud, Mylène (Criminologie, 1992)
The interest in understanding and analyzing the situation of native women within the penal process is recent and seems to be limited by the inordinate attention paid by researchers to the overrepresentation of native women. This article is an account of the findings and analyses made to date in this recent sector of research. It presents an inventory of the principal data concerning the confrontation of native women with the penal process. It proposes a synthesis of the principal analyses of the problems of native women with the system of justice by presenting a critical analysis of the socio-structural model of LaPrairie.
Keywords: amériques; approches et analyses; canada; cours; criminologie; discipline; droit; droits des femmes*; droits des femmes* autochtones; histoire et politique; intersectionnalité; justice sociale; pol4105; premier cycle; racisme; régions géographiques; science politique et droit; sciences humaines; sexisme; système colonial; systèmes d'oppressions; thématiques; violences

L'Envers de la nuit: les femmes contre la pornographie - Lederer, Laura; Audy, Monique; Dufresne, Martin (Les éditions du remue-ménage, 1983)
Les textes Morgan, R. (1983). La pornographie et le viol : théorie et pratique et Dworkin, A. (1983). Pour les hommes, liberté d’expression. Pour les femmes, silence, s’il vous plaît ont été donné en lecture au corus SEX1911.
Keywords: 1900-1999; amériques; approches et analyses; corps; cours; discipline; droit; féminisme pop; premier cycle; psychologie; périodes historiques; régions géographiques; science politique et droit; sciences humaines; sex1911; sexisme; sexualité; systèmes d'oppressions; thématiques; violences; états-unis

The Destruction of American Indian families - Unger, Steven (Association on American Indian Affairs, 1977)
Responding to the need for a comprehensive source of information regarding the separation of American Indian children from their families, this book presents essays which: examine the Indian child-welfare crisis in contemporary, legal, and historical perspectives; document the human cost of the crisis to Indian parents, children, and communities; and report on innovative programs designed and implemented by the Indian tribes themselves. Specifically, this book includes the following sections and essay titles: (1) Contemporary Overviews ("The Destruction of American Indian Families" and "The Role of the Federal Government: A Congressional View"); (2) Historical Perspectives ("The Effects of Boarding Schools on Indian Family Life: 1928" and "'Kid Catching' on the Navajo Reservation: 1920"); (3) The Human Cost ("'The Drunken Indian': Myths and Realities"; "The Wasted Strengths of Indian Families", "The Human Cost of Removing Indian Children from Their Families", "Child-Welfare Services to Indian People in the Albuquerque Area", "Indian Child Welfare in Oregon", "The Ravage of Indian Families in Crisis", "The Question of Best Interest", and "The Placement of American Indian Children–The Need for Change"); (4) A Legal Perspective ("Parent and Child Relationships in Law and in Navajo Custom"); (5) Tribal Actions ("Indian Children and Tribal Group Homes: New Interpretations of the Whipper Man" and "Tribal Resolutions"). (JC)
Keywords: american indian families; amériques; approches et analyses; autochtones; cours; discipline; droit; famille; his4443; histoire et politique; premier cycle; racisme; racisme systémique; residential schools; régions géographiques; science politique; science politique et droit; sciences humaines; sociologie; système colonial; systèmes d'oppressions; thématiques; violence coloniale; violence systémique; violences; états-unis

Pornography, civil rights, and speech. (the 1984 Francis Biddle Memorial Lecture, Harvard Law School, April 5, 1984) (transcript) - MacKinnon, Catharine A. (Harvard Civil Rights-Civil Liberties Law Review)
Keywords: 1900-1999; 1980-1989; amériques; approches et analyses; corps; cours; discipline; droit; histoire et politique; patriarcat; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; science politique et droit; sex1911; sexisme; sexualité; systèmes d'oppressions; thématiques; violences; états-unis